Exploración de las propiedades psicométricas de la Batería Montreal de Evaluación de Amusia en una muestra de sujetos con epilepsia de lóbulo temporal. - Toledo-Fernández, Aldebarán; Salvador-Cruz, Judith (Salud Mental)
Background The Montreal Battery of Evaluation of Amusia (MBEA) is a newly developed instrument to assess music perception and memory, associated to temporal lobe functioning. The non-symptomatic temporal lobe epilepsy is a prevalent condition in Mexico, and it gives an opportunity to test the MBEA, considering the fact that epileptic seizures can cause neuropsychological impairment according to lobar localization and hemispherical lateralization of the epileptogenic foci. Objective To explore the psychometric and diagnostic properties of the MBEA. Method Two non-probabilistic samples of 31 control subjects and 22 cases with non-symptomatic temporal lobe epilepsy were assessed with the MBEA. Data from the original validation were used to compare with the control group. Results Analysis with t test showed significantly lower performances in the case group relative to controls, and a general lower performance of controls compared to the norm. There was no significant difference in performance between cases with left epileptogenic foci and cases with right epileptogenic foci. ROC curve analysis showed questionable properties of sensitivity and specificity in the MBEA. Discussion and conclusion Impairments in music perception were found in cases, although theoretical inconsistences with respect to relation between impaired functions were also detected. The performance of the control group relative to the norm aims to the continuation of the validation process, considering cultural differences. The MBEA seems to be a poor measure in terms of sensibility and specificity for the detection of amusic impairments in subjects with non-symptomatic temporal lobe epilepsy, and its utility for determining hemispheric lateralization of epileptogenic foci remains uncertain.